Efficiency of Applying the Cryopreserved Embryonic Neuronal Cells in Combined Treatment of Sclerotic Macular Dystrophy - Demin, Yu. A.; Petrenko, A. Yu.; Litvinova, L. V. (Problems of Cryobiology and Cryomedicine, 2004)
There has been demonstrated a high clinical efficiency of application of cryopreserved embryonic neuronal cells in treatment of sclerotic macular dystrophies by the methods of visometry, perimetry, oculography.